Ação e espírito: duas perspectivas sobre a capacidade de julgar em Hannah Arendt - Palandi, Krishna Lila (2019)
The present dissertation aims to determine, as closely as possible, the capacity of judgment according to Hannah Arendt. The way she approached this ability has fluctuated over time, so we can distinguish in her work two perspectives on this capacity. At first, Arendt addresses the capacity of judgment under the conceptual context of his theory of action. In a second moment, it's approached under the conceptual context of the life of the mind. This difference in context in which the capacity of judgment is analyzed instigated the philosophical debate that, perceiving the change of perspective of analysis, asks if there is coherence between both perspectives. Thus, the search for determining the capacity of judgment also demands the analysis of conceptual coherence between the mentioned approaches. Under the context of action theory, Arendt was able to determine what the capacity of judgment is. This determination happens when Arendt synthesizes, in the same capacity, aristotelian phronesis with the kantian capacity to judge reflexively. However, in this context it is not possible to clearly delimit the relationships between mind capacities among themselves, especially between the capacities of imagining and judging. This delimitation will only be possible after Arendt has investigated the life of the mind as a whole. Judgment in this context is described as one of the three fundamental activities of the mind, along with thought and will, and in close relationship with two other mind capacities, imagination and common sense. The relationships that mind capacities establish with each other have allowed Arendt to clarify some points that, under the context of action theory, would remain confusing, as well as explain how judgments are made effective. The change in perspective under which the capacity of judgment was described did not imply a conceptual split, nor the abandonment of a prior conception over a new one. In analyzing the capacity of judgment from two perspectives, Arendt provides a broad and coherent overview through which we can determine, besides what is the capacity of judgment, how she judges.